2021
DOI: 10.1177/09697330211003231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Covid-19 on ethical sensitivity

Abstract: Background: In the midst of the Covid-19 pandemic, healthcare workers increasingly encounter serious ethical issues that negatively affect their professionalism. Purpose: The study aims to examine the ethical sensitivity levels of physicians and nurses working in surgical units during the Covid-19 pandemic and the associating factors. Method: The sample of this cross-sectional online questionnaire–based study consists of 161 healthcare workers working at the surgical units in Turkish hospitals. The data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Outside the workplace, while mainstream media extolled nurses as heroes, some nurses endured stigmatizing attitudes by those viewing them as virus carriers. Therefore, community support for nurses is crucial during an epidemic ( 51 ), and policy-makers should address the barriers that create ethical challenges for nurses fighting COVID-19 ( 52 ). The study showed that a high level of social support and recognition for healthcare workers in public health emergencies could be shealing ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outside the workplace, while mainstream media extolled nurses as heroes, some nurses endured stigmatizing attitudes by those viewing them as virus carriers. Therefore, community support for nurses is crucial during an epidemic ( 51 ), and policy-makers should address the barriers that create ethical challenges for nurses fighting COVID-19 ( 52 ). The study showed that a high level of social support and recognition for healthcare workers in public health emergencies could be shealing ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Under these conditions, health care professionals and managers have difficulty making ethical decisions. 19 …”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to the need to assess nurses' moral sensitivity and courage in their professional practice, identify any deficiencies and errors, and address them with appropriate interventions. 19 …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the ethical sensitivity of nursing students ranged from moderate to high (Borhani et al, 2016;Kilic Akca, Simsek, Efe Aslan, Senturk & Akca, 2017;Tuvesson & Lützén, 2017;Uncu & Güneş, 2021). Mert, Sayilan, Karatoprak & Baydemir (2021) examined the ethical sensitivity of healthcare workers in surgical clinics during the Covid-19 pandemic and found that they had a moderate level of ethical sensitivity. In another study evaluating moral sensitivity in nurses caring for patients with Covid-19, the nurses were reported to have a high level of moral sensitivity (Khodaveisi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%